SENIOR HIGH SCHOOL TEACHERS’ CHALLENGES AND COPING STRATEGIES IN TEACHING LITERATURE IN ONLINE ENVIRONMENT - Andriani, Erina (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
The teaching-learning process in Indonesia was mostly done online due to the Covid-19 pandemic. This sudden shift caused challenges for EFL teachers. Aside from providing linguistic lessons, EFL teachers also struggled in providing literature lessons, as it had distinct ways of teaching from linguistics. However, only a few studies researched the teachers’ challenges in teaching literature online and the ways they solved them. Therefore, this study aims to explore the teachers’ challenges in teaching literature in an online environment and their strategies to deal with them. This study used a narrative inquiry method and the data were gathered with a semi-structured interview from senior high school teachers. the results showed that the teachers faced challenges with their technology uses, including internet, websites, applications, and gadgets; students, including their internet, understanding, and participation; and subject delivery, including material adjustments, students’ interests, and accessible activities. Teachers’ strategies were: having asynchronous classes, posting materials ahead, utilizing WhatsApp, helping students’ technology experience, assisting their online learning, providing accessible learning activities, using familiar literary works, and giving less demanding activities. This study can help the teachers to identify their challenges in teaching literature in an online environment and find the solutions.